Relationship between serum iron, zinc, calcium, and HIF-1a—comparative analysis of 2 regions and 4 ethnic groups in China - Guo, Yan; Lu, Zhong-Sheng; Zhang, Xue-Cheng; Zhang, Qiang; Liu, Xiao; Chen, Jie; Zhang, Meng-Lan (Frontiers in Nutrition, 2024)
Background ： Altitude illness has serious effects on individuals who are not adequately acclimatized to high-altitude areas and may even lead to death. However, the individualized mechanisms of onset and preventive measures are not fully elucidated at present, especially the relationship between altitude illness and elements, which requires further in-depth research.Methods:Fresh serum samples were collected from individuals who underwent health examinations at the two hospitals in Xining and Sanya between November 2021 and December 2021. The blood Zn, Fe and Ca concentrations, as well as HIF-1α concentrations, were measured. This study conducted effective sample size estimation, repeated experiments, and used GraphPad Prism 9.0 and IBM SPSS version 19.0 software for comparative analysis of differences in the expression of elements and HIF-1α among different ethnic groups, altitudes, and concentration groups. Linear regression and multiple linear regression were employed to explore the relationships among elements and their correlation with HIF-1α.Results:This study included a total of 400 participants. The results from the repeated measurements indicated that the consistency of the laboratory test results was satisfactory. In terms of altitude differences, except for Fe , which did not show significant variance between low and high altitude regions, Zn, Ca, and HIF-1 α elements all exhibited notable differences between these areas. When grouping by the concentrations of elements and HIF-1 α , the results revealed significant variations in the distribution of zinc among different levels of iron and HIF-1α . The outcomes of the linear regression analysis demonstrated that calcium and zinc, iron and HIF-1α, calcium and HIF-1α, and zinc and HIF-1α displayed substantial overall explanatory power across different subgroups .Finally, the results of the multiple linear regression analysis indicated that within the high-altitude population, the Li ethnic group in Sanya, and the Han ethnic group in Sanya, the multiple linear regression model with HIF-1 α as the dependent variable and elements as the independent variables exhibited noteworthy overall explanatory power .The levels of typical elements and HIF-1 α in the blood differ among various altitudes and ethnic groups, and these distinctions may be linked to the occurrence and progression of high-altitude illness.